POTENTIAL ROLE OF HEAT SHOCK PROTEINS 60, 70, AND 90 IN THE AGING AMONG POPULATION OF PUNJAB-PAKISTAN - RIAZ, A; NOREEN, B; QAISER, A; BILAL, N; ANWAR, MZ; HADI, F; MAQBOOL, T; INAMULLAH, .; SHAKOORI, TA; MUSTAFA, I; et al. (Biological and Clinical Sciences Research Journal, 2023)
Aging can be characterized as the collision of cellular and organ-destructive processes over the years with actions that maintain homeostasis, vitality, and longevity. The current study was based on an assessment of various indicators of stress, Heat shock proteins and antioxidants in elderly subjects to identifying their significance in ageing. It was aimed to increase the heat shock proteins, decreased antioxidants and vitamins responsible for ageing. A total of 100 individuals were recruited in the current study consisting of 50 young control and 50 older people. The significance of HSPs (60, 70, 90) and oxidative and antioxidant markers, were analyzed through laboratory tests and ELIZA kits using serum samples. The results were evaluated through an independent t-test in SPSS version 16. Elder group showed a significantly higher level of HSP-60, HSP-70, and HSP-90 than the control group. According to study results, the anti-oxidant profile, which includes SOD, CAT, and GSH, exhibited a dramatically declining trend in the aged population. MDA and NO, which are indicators of oxidative stress, were also higher in the elderly population than in the young. The study also showed that the elderly had lower vitamin A, C, D, and E levels than the young. The results reflect the increased level of inflammatory markers specifically heat shock proteins in old people compared to healthy control. It is indication that increased level of heat shock proteins are responsible for aging. It can be cured by limiting the heat shock proteins.